(3eNJUQ CfhGQ GdHQhb aj CfhGY GdaQhbs - (3CHh YHO Gddg eMeO Hf CHh GdbGSe Hf YHO GdSdGe Hf Lejd GdRHYi GdJhfSi GdeGdcjs; (3GdbQGaj , CMeO Hf GOQjS Hf YHO GdQMef, TgGH GdOjf CHh GdYHGS,J (B684 (3g` s ((3CMeO Hf YeQ GdCRgQi s)
(3ChdgG (B:s
(3bGdhG GdEUMGM haGQb Cgd GdZi ef Cgd GdUdGM s
(3BNQgG (B:s
(3GdCdaGX GdUQjMI ai GdOYG JSJYed ai ZjQg hdjS eG ai GdMOjK ef gPG GdHGH s
(3bdjd GdfbWs
(3hQO GdYfhGf GdCUdi ai cTa GdXfhf(B186/1s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3CUhd Gdabgs